2014
DOI: 10.1093/bja/aeu086
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical modelling of fibrinogen supplementation with therapeutic plasma, cryoprecipitate, or fibrinogen concentrate

Abstract: BackgroundWe aimed to create a theoretical tool to model the effect of three haemostatic agents containing fibrinogen (therapeutic plasma, cryoprecipitate, and fibrinogen concentrate) on the patient's plasma fibrinogen level.MethodsA mathematical model was developed step-wise. The relationship between the amount of haemostatic agent and plasma fibrinogen level was plotted for each agent. A fibrinogen concentration simulator (FCSamount) was developed, where the amount of haemostatic agent was calculated from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 32 publications
2
85
0
1
Order By: Relevance
“…Fibrinogen can be replaced with: fibrinogen concentrate (FC), cryoprecipitate or plasma, each containing different amounts of fibrinogen: 20g/L, 8-16g/l and 2g/L, respectively, and therefore different volumes are required to achieve replacement (65). A study by Rourke et al (37) demonstrated that standard protocol driven transfusion ratios were ineffective in maintaining fibrinogen levels and the addition of cryoprecipitate was required.…”
Section: Fibrinogen Replacement As Part Of a Mhpmentioning
confidence: 99%
“…Fibrinogen can be replaced with: fibrinogen concentrate (FC), cryoprecipitate or plasma, each containing different amounts of fibrinogen: 20g/L, 8-16g/l and 2g/L, respectively, and therefore different volumes are required to achieve replacement (65). A study by Rourke et al (37) demonstrated that standard protocol driven transfusion ratios were ineffective in maintaining fibrinogen levels and the addition of cryoprecipitate was required.…”
Section: Fibrinogen Replacement As Part Of a Mhpmentioning
confidence: 99%
“…67 There is a perceived risk of triggering a thromboembolic event associated with fibrinogen supplementation, and that administering excessive fibrinogen, particularly with high thrombin generation, may increase the risk of systemic microthrombogenicity. However, post hoc analysis of a randomized clinical trial of fibrinogen concentrate reported fibrinogen supplementation was not associated with significant alterations of hemostatic parameters.…”
Section: Fibrinogen Dosingmentioning
confidence: 99%
“…It was also reported that abnormalities of R and MA values measured by TEG® were independent predictive factors for poor outcome [33][34][35][36]. It has been demonstrated that prolongation of CFT and a decrease in MCF which indicate a decrease in platelet count measured by ROTEM® were correlated more strongly with poor outcome than with mortality calculated with the Trauma and Injury Severity Score (TRISS) equation [32,37]. It has been reported that a decrease in fibrinogen level which is detectable in the early stage of coagulopathy was also correlated with poor outcome, suggesting the use of fibrinogen level as the standard for administration of cryoprecipitate and fibrinogen preparations [30].…”
Section: Reports On the Relationship Between The Use Of Viscoelastic mentioning
confidence: 99%